Advocating for Antiracist Approaches to Writing in the Canadian Postsecondary Context : A Roundtable Discussion - Brancato , Emilie; Prescott-Brown , Marci; Natarajan , Srividya; Penney, Mandy; Sapuridis , Effie; Torbica, Maša (SKRIB, 2024)
On Tuesday May 3rd 2022, over 70 writing centre professionals, tutors, and students attended a virtual session titled “Advocating for Antiracist Approaches to Writing in the Canadian Postsecondary Context” to learn from and uplift six colleagues who have extensive experience doing antiracist advocacy work. Insights from a seventh colleague who was unable to attend are included here. As writing centre professionals, tutors, and students, we contribute to a colonial education system that has embedded within itself systemic racism and white supremacy. Writing and the English language have historically been—and continue to be—used to oppress and exclude Black, Brown, Indigenous, racialized, queer, trans, poor, and disabled peoples. At the same time, writing and language can be—and are being—leveraged for anti-oppressive means and ends. How can we, working from and within our respective writing centre contexts, use our engagement in this critical conversation about antiracist writing to create liberatory change? How can we engage in meaningful advocacy with faculty, administrators, and other key players to make a difference to the way that writing and language are taken up across academic institutions? The panelists share their stories, goals, specific actions they have taken, and advice for advocacy to address these questions.